Biopharmaceutical factory of the future. (June 2015) - Alldread, Richard; Robinson, Jonathan
The growth in stratified medicine and the economic pressures to reduce capital investment, cost of development and cost of goods are forcing a change in how biopharmaceutical manufacturing plants are designed, built and operated. It is likely that future manufacturing facilities will be built on the principle of flexibility and make even greater use of single use technology, continuous manufacturing and alternative expression systems. Large scale production will in many cases be achieved by the 'scale out' of multiple smaller facilities rather than the 'scale up' to large capacity plants. Some of the core technology required to achieve this vision is already available though further development is required in many areas.